Organizational health and its role in achieving institutional excellence in Yemeni government universities from the point of view of academic and administrative leaders for the year 2022- 2021 - Qadhah, Marwa Hammoud Muhammad; Alamery, Abdulaziz Abdulhady (Journal of Educational and Psychological Sciences, 2023)
The research aimed to identify the role of organizational health in achieving institutional excellence in Yemeni government universities from the point of view of academic and administrative leaders. The reseachers followed the descriptive survey method, and the questionnaire was used as a tool for collecting primary data from the research sample consisting of academic leaders in (4) government universities, whose number is (438) individuals, and they represent (36.11%) of the total research popluation. The results of the research concluded that the level of availability of organizational health dimensions in Yemeni public universities in general were average, as the arithmetic mean was (3.04), and that the level of achieving institutional excellence was average, where the arithmetic mean was (3.14), and the results also showed a positive, direct correlation with statistical significance at the level (α ≤ 0.05) between organizational health and institutional excellence in Yemeni public universities, where the value of the correlation coefficient reached (0.58), and the presence of The impact of organizational health on achieving institutional excellence by (0033.%). In the light of the results, the researchers presented a number of recommendations, including that the leaders of public universities be keen to provide financial and material resources that the workers need in a timely manner, and to use the financial resources of universities efficiently and effectively, and to create a suitable work environment for workers to show their creativity and distinction in the performance of their job, duties, in addition to implementing training programs for university workers, especially in the field of developing strategic and operational plans, and working to improve and develop mechanisms and methods for providing services to students.
Keywords: organizational health; institutional excellence; public universities; Yemen